Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Literasi Matematis Siswa MAN 1 Sumedang - Pratiwi, Ana; Rosita, Neneng Tita (Suska Journal of mathematics Education, 2024)
Mathematical literacy abilities is a very important in learning mathematics, because without good mathematical literacy abilities, students will have difficulty reasoning, arguing, creating and competing in the era of globalization. One approach that can be made to improve mathematical literacy abilities is by implementing the Problem Based Learning (PBL) model in mathematics learning. This research aim is to determine the improvement in mathematical literacy abilities among students who received the PBL model compared to those who received conventional learning. The research population comprises eleventh-grade students at Sumedang State Islamic Senior High School 1, totaling 7 classes, then taken two sample classes were selected: class XI social 2 as the experimental group and class XI social 1 as the control group with a total of twenty two students in each class. The method employed is quasi-experimental, utilizing a test instrument in the form of essay type mathematical literacy ability tests. Test data was analyzed quantitatively using statistical tests. Based on the results of data analysis, it shows that there is a difference in improvment mathematical literacy abilities among students who received the PBL model compared to those who received conventional learning